Antecedents of behavioural intention towards purchasing apparel products using social media in Saudi Arabia - Alnasser, Asem Nasser H (2021)
With the latest advancement in technology, consumer behaviour has become a dynamic and ever-changing phenomenon. As a result, consumer behavioural intention studies directed exceptional interest for researchers, who seek to deeply comprehend online consumers’ purchasing behavioural intentions. Numerous models and frameworks have been proposed to better understand online consumers’ purchasing behavioural intention. These models, however, are ever-changing since online consumer behaviour is an everevolving phenomenon due to progressive technological advancements. In the Kingdom of Saudi Arabia (KSA), social media is widely used and has been adopted by many classes of the community. Instagram was used by 54% and 65% of Saudi Arabian social media platform users in 2018 and 2021, respectively. Despite having nearly 30 million Internet users, there are only 12 million online shoppers in KSA. This study aims to determine the extent to which a social media platform (i.e., Instagram) users’ perceptions about the influencers’ credibility, ease of use, attitude, and trust in the seller’s social page, influence their online purchasing behavioural intention. To this end, a quantitative method has been implemented by using a self-administered questionnaire design. In this study, the Perceived Ease of Use (PEOU), perceived usefulness (PU), trust, attitude, and credibility of influencers were the main variables, which were used to determine the behavioural intention of social media platform users in transacting an online purchase. The statistical results showed that attractiveness was found to be the least important determinant that impacting on online consumers’ purchasing behavioural intention. Therefore, practitioners should devote an appropriate amount of resources to these variables to maximise return on investment. Based on the findings of the study, it has been suggested that there should be various ways for policymakers to grow the success of online businesses and promote marketing plans for designing and implementing online businesses. Finally, strategies to increase customers' trust in conducting online purchases through social media platforms such as Instagram were emphasized in this study.